Alcohol consumption in relation to maternal deaths from induced-abortions in Ghana - Asamoah Benedict O; Agardh Anette (BMC, 2012)
Abstract Introduction The fight against maternal deaths has gained attention as the target date for Millennium Development Goal 5 approaches. Induced-abortion is one of the leading causes of maternal deaths in developing countries which hamper this effort. In Ghana, alcohol consumption and unwanted pregnancies are on the ascendancy. We examined the association between alcohol consumption and maternal mortality from induced-abortion. We further analyzed the factors that lie behind the alcohol consumption patterns in the study population. Method The data we used was extracted from the Ghana Maternal Health Survey 2007. This was a national survey conducted across the 10 administrative regions of Ghana. The survey identified 4203 female deaths through verbal autopsy, among which 605 were maternal deaths in the 12 to 49 year-old age group. Analysis was done using Statistical software IBM SPSS Statistics 20. A case control study design was used. Cross-tabulations and logistic regression models were used to investigate associations between the different variables. Results Alcohol consumption was significantly associated with abortion-related maternal deaths. Women who had ever consumed alcohol (OR adjusted 2.6, 95% CI 1.38-4.87), frequent consumers (OR adjusted 2.6, 95% CI 0.89-7.40) and occasional consumers (OR adjusted 2.7, 95% CI 1.29-5.46) were about three times as likely to die from abortion-related causes compared to those who abstained from alcohol. Maternal age, marital status and educational level were found to have a confounding effect on the observed association. Conclusion Policy actions directed toward reducing abortion-related deaths should consider alcohol consumption, especially among younger women. Policy makers in Ghana should consider increasing the legal age for alcohol consumption. We suggest that information on the health risks posed by alcohol and abortion be disseminated to communities in the informal sector where vulnerable groups can best be reached.